2013
DOI: 10.1521/ijgp.2013.63.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style Changes Following Intensive Short-term Group Psychotherapy

Abstract: In this study, we examined changes in attachment style as measured by the Relationship Scales Questionnaire before and after six weeks of intensive group psychotherapy. We also investigated whether changes in attachment style were associated with changes in interpersonal functioning. Results indicated that participants showed increases in secure attachment and decreases in fearful attachment and, to a lesser degree, preoccupied attachment styles. Change was not found in the dismissive attachment style. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…Similarly, Kinley and Reyno (2013) found improvements in secure and fearful attachment following brief group treatment. The treatment was highly structured and included elements such as practice working through painful emotions, increasing self-awareness, improving interpersonal relationships, developing coping skills, and challenging dysfunctional thinking.…”
Section: Interpersonal Learning and Attachmentmentioning
confidence: 84%
“…Similarly, Kinley and Reyno (2013) found improvements in secure and fearful attachment following brief group treatment. The treatment was highly structured and included elements such as practice working through painful emotions, increasing self-awareness, improving interpersonal relationships, developing coping skills, and challenging dysfunctional thinking.…”
Section: Interpersonal Learning and Attachmentmentioning
confidence: 84%
“…Although this may have been long held and treasured knowledge to couples therapists, research that confirms this clinical insight is still lacking. Although research has established that therapeutic intervention can influence changes in attachment style (Kinley & Reyno, ; Travis, Bliwise, Binder, & Horne‐Moyer, ), few studies have attempted to identify which in‐session behaviors are related to changes in attachment security for couples (Dalgleish, Johnson, Burgess Moser, Wiebe, & Tasca, ). The results of the current study suggest that therapists and researchers may wish to focus on the specific behaviors (accessibility, responsiveness, and engagement) that can lead to attachment‐related change for couples.…”
Section: Discussionmentioning
confidence: 99%
“…Although adult attachment styles are stable over time (Dykas & Cassidy, ), negative (or traumatic) experiences may create an insecure attachment style in previously secured individuals (Winham et al, ). With this in mind, it has been suggested that therapeutic intervention may support anxiously attached or avoidantly attached individuals to improve attachment security (e.g., Kinley & Rayno, ; Marmarosh, ).…”
Section: Introductionmentioning
confidence: 99%